2023
DOI: 10.1177/20420986231188836
|View full text |Cite
|
Sign up to set email alerts
|

Funding and financial sustainability of pharmacovigilance: suggested models for funding pharmacovigilance in resource-limited African countries

Abstract: Background: An important factor hindering the growth of pharmacovigilance (PV) in resource-limited settings is the lack of adequate funds to establish a functional National Pharmacovigilance System. Consequently, the crucial function of monitoring and ensuring the availability of safe medicines in these settings cannot be guaranteed considering the peculiarities of diseases and medicines used. Objectives: The objective of this paper is to provide an overview as to the availability of potential sources of funds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…This possibly explains the small extent of African PV schemes in terms of therapeutic areas covered, the number of ICSRs submitted to VigiBase®, and the scope of PV activities [ 7 ]. Isah et al found that in addition to the significant donor funding, most African PV systems lack independence from regulatory agencies regarding operational and fiscal governance, limiting their operability [ 24 ]. The observed 2.1% African literature output mirrors the mere 0.88% African ICSR contribution to the global ADR database, VigiBase® [ 7 ] indicating the lack of investment in the field.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This possibly explains the small extent of African PV schemes in terms of therapeutic areas covered, the number of ICSRs submitted to VigiBase®, and the scope of PV activities [ 7 ]. Isah et al found that in addition to the significant donor funding, most African PV systems lack independence from regulatory agencies regarding operational and fiscal governance, limiting their operability [ 24 ]. The observed 2.1% African literature output mirrors the mere 0.88% African ICSR contribution to the global ADR database, VigiBase® [ 7 ] indicating the lack of investment in the field.…”
Section: Reviewmentioning
confidence: 99%
“…Several issues need to be addressed to redress the observed PV limitations in Africa. Firstly, firm regulatory policy and enforceable PV legislation need to be adopted to ensure adequate funding and authority to the local regulatory authorities (RAs) [ 24 , 26 ]. RAs and especially marketing authorization holders (MAHs) should be legally accountable for the provision of risk management plans for any registered medicine in Africa as occurs in ICH territories.…”
Section: Reviewmentioning
confidence: 99%